Two new species of blue-eyed Trimma (Pisces; Gobiidae) from New Guinea - Winterbottom, Richard; Erdmann, Mark V. (Zootaxa, 2018)
Two new species of Trimma are described from New Guinea, one at the southeastern end at Normanby Island (Milne Bay Province), the other from Cendrawasih Bay, West Papua, on the north-east coast. The dorsal surface of the eye of both species is blue in life, a characteristic not reported elsewhere in the genus. Although the two species look very similar in life, and both occupy similar mesophotic rubble habitats in the 50-70 m depth range, they are separated both genetically (7.7% pairwise genetic distance in COI) and morphologically. Trimma blematium has 16 pectoral fin rays, a branched 5th pelvic fin ray, and 7 papillae in row p, whereas T. meityae has 17–18 pectoral fin rays, an unbranched 5th pelvic fin ray, and 8 papillae in row p. In live specimens, the blue colour over the top of the eyes is much darker in T. blematium than in T. meityae. The type localities are separated by almost 2,000 km (straight-line distance).